Molecular evolution and nucleotide sequences of the maize plastid genes for the alpha subunit of CF1 (atpA) and the proteolipid subunit of CF0 (atpH) - Rodermel, S.R; Bogorad, L (Genetics (Austin), 1987)
The nucleotide sequences of the maize plastid genes for the α subunit of CF1 (atpA) and the proteolipid subunit of CF 0 (atpH) are presented. The evolution of these genes among higher plants is characterized by a transition mutation bias of about 2:1 and by rates of synonymous and nonsynonymous substitution which are much lower than similar rates for genes from other sources. This is consistent with the notion that the plastid genome is evolving conservatively in primary sequence. Yet, the mode and tempo of sequence evolution of these and other plastid-encoded coupling factor genes are not the same. In particular, higher rates of nonsynonymous substitution in atpE (the gene for the ∊ subunit of CF1) and higher rates of synonymous substitution in atpH in the dicot vs. monocot lineages of higher plants indicate that these sequences are likely subject to different evolutionary constraints in these two lineages. The 5′- and 3′ transcribed flanking regions of atpA and atpH from maize, wheat and tobacco are conserved in size, but contain few putative regulatory elements which are conserved either in their spatial arrangement or sequence complexity. However, these regions likely contain variable numbers of "species-specific" regulatory elements. The present studies thus suggest that the plastid genome is not a passive participant in an evolutionary process governed by a more rapidly changing, readily adaptive, nuclear compartment, but that novel strategies for the coordinate expression of genes in the plastid genome may arise through rapid evolution of the flanking sequences of these genes.